2014
DOI: 10.1152/ajpendo.00656.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acylcarnitines activate proinflammatory signaling pathways

Abstract: Incomplete β-oxidation of fatty acids in mitochondria is a feature of insulin resistance and type 2 diabetes mellitus (T2DM). Previous studies revealed that plasma concentrations of medium- and long-chain acylcarnitines (by-products of incomplete β-oxidation) are elevated in T2DM and insulin resistance. In a previous study, we reported that mixed d,l isomers of C12- or C14-carnitine induced an NF-κB-luciferase reporter gene in RAW 264.7 cells, suggesting potential activation of proinflammatory pathways. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(228 citation statements)
references
References 24 publications
8
218
2
Order By: Relevance
“…In contrast, short chain acylcarnitines were relatively decreased in IFN-␥-stimulated Irgm1-deficient BMM. Because LC-AC have pro-inflammatory properties (47)(48)(49)(50)(51), these data reinforce the finding that in IFN-␥-primed Irgm1-deficient macrophages, metabolic changes occur that are proinflammatory and typically only seen in macrophages following activation with LPS. We also exposed the cells to LPS and IFN-␥ to examine how the metabolic changes in IFN-␥-primed, Irgm1-deficient cells might compare with those in fully activated macrophages.…”
Section: Resultssupporting
confidence: 75%
“…In contrast, short chain acylcarnitines were relatively decreased in IFN-␥-stimulated Irgm1-deficient BMM. Because LC-AC have pro-inflammatory properties (47)(48)(49)(50)(51), these data reinforce the finding that in IFN-␥-primed Irgm1-deficient macrophages, metabolic changes occur that are proinflammatory and typically only seen in macrophages following activation with LPS. We also exposed the cells to LPS and IFN-␥ to examine how the metabolic changes in IFN-␥-primed, Irgm1-deficient cells might compare with those in fully activated macrophages.…”
Section: Resultssupporting
confidence: 75%
“…Of these, 66 showed statistically significant changes because of NTHI infection. Acylcarnitines stimulate proinflammatory responses, in part, through IL-8 (73). However, acylcarnitines were not detected.…”
Section: Metabolite Profile Indicates That the Middle Ear Is Immunosumentioning
confidence: 89%
“…Our previous work has shown that long-chain fatty acylcarnitines activate proinflammatory signaling pathways in RAW 264.7 murine macrophages (1,29) and in HCT-116 cells (29), and blunt the insulin signaling pathway in both murine C 2 C 12 and human primary skeletal muscle cells (2). These activities were found to occur at initial extracellular concentrations of C14 carnitine and C16 carnitine as low as 5 M. Thus, whether or not these metabolites contribute to, or exacerbate, disease phenotypes or normal physiological processes remains an open question.…”
mentioning
confidence: 99%